Gaze and Denouncement: Social control and moral sanction in 4 Months, 3 Weeks and 2 Days - Ayuso Ros, Francisco Miguel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
4 Months, 3 Weeks and 2 Days by Cristian Mungiu, 2007 is a film set in Communist Romania during the final years of the Nicolae Ceaușescu era and tells the ordeal of two university students on the day that one of them is about to undergo an illegal abortion. The discursive strategies of this film are in line with a realist approach, which avoids all those resources of mise en scène that entail a greater illustrative presence. However, there is a scene in the film that does not follow this approach, and generated some controversy in specialised media.